Recovering Bioactive Compounds from Olive Oil Filter Cake by Advanced Extraction Techniques - Jesús Lozano-Sánchez (International Journal of Molecular Sciences, 2014)
The potential of by-products generated during extra-virgin olive oil (EVOO) filtration as a natural source of phenolic compounds (with demonstrated bioactivity) has been evaluated using pressurized liquid extraction (PLE) and considering mixtures of two GRAS (generally recognized as safe) solvents (ethanol and water) at temperatures ranging from 40 to 175 °C. The extracts were characterized by high-performance liquid chromatography (HPLC) coupled to diode array detection (DAD) and electrospray time-of-flight mass spectrometry (HPLC-DAD-ESI-TOF/MS) to determine the phenolic-composition of the filter cake. The best isolation procedure to extract the phenolic fraction from the filter cake was accomplished using ethanol and water (50:50, v/v) at 120 °C. The main phenolic compounds identified in the samples were characterized as phenolic alcohols or derivatives (hydroxytyrosol and its oxidation product), secoiridoids (decarboxymethylated and hydroxylated forms of oleuropein and ligstroside aglycones), flavones (luteolin and apigenin) and elenolic acid derivatives. The PLE extraction process can be applied to produce enriched extracts with applications as bioactive food ingredients, as well as nutraceuticals.